How understanding past landscapes might inform present‐day site investigations: a case study from Dogger Bank, southern central North Sea. Issue 4 (1st June 2017) - Cotterill, Carol; Phillips, Emrys; James, Leo; Forsberg, Carl‐Fredrik; Tjelta, Tor Inge
ABSTRACT: The integration of geophysical and geotechnical datasets acquired during a site survey for the Dogger Bank wind farm has enabled a new litho‐ and seismo‐stratigraphy to be established. Although previously believed to be a relatively simple "layer‐cake", the data reveal that the sedimentary sequence within the foundation zone includes a complex series of buried landscapes with implications for both foundation siting and design. The most significant is a Weichselian glacially derived landscape dominated by a large thrust‐block moraine complex buried beneath a thin Holocene sequence. This glacial landscape profoundly affects the structure and physical properties of sediments within the foundation zone due to locally intense glaciotectonic deformation and the occurrence of sub‐aerially desiccated horizons recording fluctuating palaeo‐climatic conditions. Understanding these landscapes, coupled with the geophysical and geotechnical data, enables the development of a predictive "geo‐model" that may be used to target areas of uncertainty, reducing the requirement for boreholes (over Cone Penetration Tests) at every potential foundation location.